Pengaruh Sikap Belajar Dan Efikasi Diri Terhadap Prestasi Belajar Kimia Siswa Kelas XI MIPA Madrasah Aliyah Negeri Di Kabupaten Bekasi - Sriatun, Surip (Gema Widyakarya bekerjasama dengan Persatuan Guru Republik Indonesia (PGRI) Daerah Khusus Ibukota Jakarta, 2018)
The purpose of this study was to analyze the influence of learning attitudes and self-efficacy of students on Chemistry learning achievement. The research method used is a survey research method with multiple regression analysis techniques. The sample of the study amounted to 84. The results concluded: (1) There is a significant influence together with learning attitudes and self-efficacy on learning achievement Chemistry students of Madrasah Aliyah Negeri in Bekasi. This is evidenced by Sig. = 0,000 <0,05 and Fhitung = 228,067 .. (2) There is a significant influence of learning attitude toward students' Chemical learning achievement of MAN in Bekasi Regency. This is evidenced by Sig. = 0,000 <0,05 and t-count = 6,592. (3) There is a significant effect of self-efficacy on learning achievement of Chemistry of MAN students in Bekasi Regency. This is evidenced by Sig. = 0,000 <0,05 and t-count = 7,975. The implications of this research are: (1) There is a significant direct influence on the learning attitudes and self-efficacy on Chemistry achievement of the students of Madrasah Aliyah Negeri in Bekasi Regency, it shows that to improve the achievement of good chemistry learning can be done with improving student learning attitude self-efficacy. (2) There is a significant influence of learning attitudes toward Chemical learning achievement, it shows that to create learning achievement Chemistry can be done by improving student's learning attitude (3) There is a significant influence self-efficacy to learning achievement Chemistry, this shows to improve learning achievement can create good self-efficacy.